Money Politics: The Problem of Good Governance in Ese-Odo Local Government Area, Ondo State, Nigeria - Tolo, David; Abolarin, Oluwakemi Ibidapo (International Journal of Shari'ah and Corporate Governance Research, 2019)
This study examined critically how money and gifts have been used to influence the electorates during elections in Ese-Odo Local Government Area of Ondo State. Politicians in Nigerian society, especially in Ese-Odo LGA seem to have their ways in forcing themselves into seat of power by manipulating the thought of the electorates thereby engaging them into vote-buying and vote-selling. The population for study consisted of 213600 citizens. The sample consisted of four hundred (400) respondents. Three research questions were raised for the purpose of the study. The data that were retrieved from the respondents were three hundred and ninety-eight. Descriptive statistics was used to analyse the data and one hypothesis was also tested. The study found out that using money and other gifts by the politicians to influence the electorates is one of the major reasons for bad governance in Ese-Odo LGA. The study concluded that money politics has brought a great setback to democracy and has hampered the development of the masses and that of the society at large. The study, there for, recommended that for there to be free and fair elections in the society, the electorates must be enlightened on the civic rights of the electorates so as not to get involved in money politics. This will enable the electorates to vote for any political aspirant of their choice. Electoral laws should be strictly adhered to, and any electoral officer who is involved in using the period of elections as a means of extorting money from the political contestants should be dealt with. However, any political member who is caught in the act of vote-buying should be severely punished according to electoral laws. By doing this, the masses will be able to secure their well-being and that of the generations yet to come for sustainable development.